A prospective study of the effect of fasting during the month of Ramadan on depression and diabetes distress in people with type 2 diabetes. (July 2019) - Al-Ozairi, Ebaa; AlAwadhi, Manar M.; Al-Ozairi, Abdulla; Taghadom, Etab; Ismail, Khalida
Abstract: Aims: Depression in diabetes has been associated with hyperglycemia and an increase risk for metabolic disorder complications. Ramadan is a period of self-discipline, self control, and spirituality, which has shown benefits in physical, mental, and social well being. The aim of this study is to examine the association between fasting during the month of Ramadan and depression. Methods: Data from 463 participants were collected at three time points. A paired t -test was used to examine the difference between PHQ-9 score and difference of PAID score before and after Ramadan to measure depression. A multivariable regression with adjusting for potential confounders was used to study the association between fasting and depression. Results: The difference in PHQ-9 score before and after Ramadan was −3.5 points (95% Confidence Interval (CI) −4.05 to −2.95). The difference in PAID score before and after the Ramadan was −5.02 points (95% CI −6.38 to −3.69). For every one year increase in diabetes diagnosis PHQ-9 score decreased by 0.09 (95% CI −0.17 to 0.003) after Ramadan. Female participants had 1.17 more points (95% CI −0.23 to 0.02) decrease in PHQ-9 score compared to male participants. Conclusion: Improving depression in people with diabetes is crucial in controlling blood glucose and metabolic disorder complications in people with diabetes. People with diabetes who experience depression may improve their depression by increasing self discipline, self control, and manage disease.